ENCRYPTED QR CODE FOR BRAND AUTHENTICATION: ENQRURE MOBILE APPLICATION DEVELOPMENT AND EVALUATION (Journal of Digital System Development, 2023)
Counterfeit products pose a growing concern for brand owners and consumers due to their adverse effects on user experience and brand value, leading to unsatisfied customers, negative publicity, and even potential health risks. This paper addresses the growing issues surrounding fake goods, which negatively affect customers and brand owners, including harmed user experiences, tarnished reputations, and potential health risks. The work proposed an encrypted QR code emphasising encryption techniques embedded in a mobile application with a friendly user interface and seamless interaction with existing authentication mechanisms to resolve this problem. The application aims to detect counterfeit goods, protect brand reputation, and increase consumer confidence by guaranteeing product authenticity. The study conducted a usability evaluation with 30 volunteers. The results indicated that enQRure proved to be a valuable and user-friendly application. Respondents expressed satisfaction with the application’s feature that facilitates product authentication. Feedback analysis on features offered by enQRure, such as product registration, product authentication, and encrypted QR code generation processes, revealed that most respondents found them straightforward and useful. They perceived enQRure as an effective means to authenticate products, aligning with their preferences and needs.